Green and sustainable finance: Principles and practice in banking, investment and insurance - Thompson, Simon (London Kogan Page Ltd., 2025)
Green and Sustainable Finance by Simon Thompson is the definitive guide for financial analysts, investment managers and banking professionals who want to integrate sustainability into every financial decision.